Harzianopyridone Supplementation Reduced Chromium Uptake and Enhanced Activity of Antioxidant Enzymes in Vigna radiata Seedlings Exposed to Chromium Toxicity - Shah, Anis Ali; Shah, Adnan Noor; Bilal Tahir, Muhammad; Abbas, Asad; Javad, Sumera; Ali, Sajid; Rizwan, Muhammad; Alotaibi, Saqer S.; Kalaji, Hazem M.; Telesinski, Arkadiusz; Javed, Talha; AbdElgawad, Hamada (Frontiers in Plant Science, 2022)
This study explains the scarce information on the role of harzianopyridone (HZRP) in the alleviation of chromium (Cr) stress alleviation in Vigna radiata (L.). To this end, V. radiata seedlings primed with HZRP at 1 and 2 ppm were exposed to 50 mg kg–1 Cr for 30 days. Cr stress reduced growth, chlorophyll (Chl) content, net photosynthetic rate, gas-exchange attributes along with enhanced oxidative damages, i.e., electrolyte leakage (EL), hydrogen peroxide (H2O2), and malondialdehyde (MDA). Application of HZRP enhanced intercellular carbon dioxide (CO2) concentration, stomatal conductance, and net photosynthetic rate with decreased activity of the chlorophyllase (Chlase) enzyme in V. radiata seedlings exposed to Cr stressed conditions. To maintain Cr-induced oxidative damages, HZRP treatment increased the levels of antioxidant metabolites (phenolic and flavonoids) and the activity of antioxidative enzymes [superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD)] in V. radiata seedlings grown in normal and Cr-polluted potted soil. In addition to this, glycine betaine content was also increased in plants grown in Cr-contaminated soil. It is proposed the potential role of supplementation of HZRP in mitigating Cr stress. Further research should be conducted to evaluate the potential of HZRP in the mitigation of abiotic stresses in plants.